Plant and pathogen genomics: essential approaches for stem rust resistance gene stacks in wheat - Jost, Matthias; Outram, Megan A.; Dibley, Kathy; Zhang, Jianping; Luo, Ming; Ayliffe, Michael (Frontiers in Plant Science, 2023)
The deployment of disease resistance genes is currently the most economical and environmentally sustainable method of crop protection. However, disease resistance genes can rapidly break down due to constant pathogen evolution, particularly when they are deployed singularly. Polygenic resistance is therefore considered the most durable but combining and maintaining these genes by breeding is a laborious process as effective genes are usually unlinked. The deployment of polygenic resistance with single locus inheritance is a promising innovation that overcomes these difficulties, while enhancing resistance durability. Due to major advances in genomic technologies, increasing numbers of plant resistance genes have been cloned enabling the development of resistance transgene stacks (RTGS) that encode multiple genes all located at a single genetic locus. Gene stacks encoding five stem rust resistance genes have now been developed in transgenic wheat and offer both breeding simplicity and potential resistance durability. The development of similar genomic resources in phytopathogens has advanced effector gene isolation and, in some instances, enabled functional validation of individual resistance genes in RTGS. Here the wheat stem rust pathosystem is used as an illustrative example of how host and pathogen genomic advances have been instrumental in the development of RTGS which is a strategy applicable to many other agricultural crop species.